2019
DOI: 10.1115/1.4042571
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Implications of Model Granularity for Design Process Simulation

Abstract: Determining a suitable level of description, or granularity, for a product or process model is not straightforward, especially since granularity can manifest in multiple ways, but it is important to capture important elements in the model without building models that are too large to understand. This article investigates the implications of model granularity choices by simulating the design process of a diesel engine on different levels of detail, comparing the results and exploring ways to account for the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Karniel and Reich demonstrated that the logic differences between process models required the simulation-based decision-making to select correct concurrent process models according to the specific process attributes (Karniel and Reich, 2009). To investigate the implications of granularity on the outcomes of process models, the simulation-based method was adopted to compare the results and explore ways to account for the differences by modeling the product development process as design structure matrices (DSMs) at different granularity levels (Maier et al , 2019). Suzuki et al presented a simulation-based process modeling tool to identify the fragility of product-based design processes and the tolerance of function-based design processes to overload situations (Suzuki et al , 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Karniel and Reich demonstrated that the logic differences between process models required the simulation-based decision-making to select correct concurrent process models according to the specific process attributes (Karniel and Reich, 2009). To investigate the implications of granularity on the outcomes of process models, the simulation-based method was adopted to compare the results and explore ways to account for the differences by modeling the product development process as design structure matrices (DSMs) at different granularity levels (Maier et al , 2019). Suzuki et al presented a simulation-based process modeling tool to identify the fragility of product-based design processes and the tolerance of function-based design processes to overload situations (Suzuki et al , 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Due to the space constraint, the figures showing optimization processes are not included. Sequential and concurrent change propagation simulations are both adopted to compare their different change propagation dynamics (Barthelemy et al , 2005; Karniel and Reich, 2009; Suzuki et al , 2012; Maier et al , 2019). In the simulations, the initial change effect for initiated changes and the threshold value for propagations are assigned with 0.6 and 0.01, respectively.…”
Section: System Implementation and Case Studymentioning
confidence: 99%
“…During this time, the approaches to creating digital models and digital twins of complex multiscale systems have proven their effectiveness [19][20][21]. The key factors in the multiscale systems of digital model design are reliability, determined by validation and verification [22]; the definition of valid interfaces and links to the experimental process [23]; the determination of the final model's details at the stage of formalizing the complex system's representation [24].…”
Section: Introductionmentioning
confidence: 99%